Ag/Au/Pt trimetallic nanoparticles with defects: Preparation, characterization, and electrocatalytic activity in methanol oxidation - Kontee Thongthai (2018)
© 2017 IOP Publishing Ltd. Two series of Ag x /Au/Pt y trimetallic nanoparticles (Ag x Au1Pt2 with x ranging from 1-5 and Ag4Au1Pt y with y ranging from 1-3) were prepared by a sequential chemical reduction method that involved the deposition of Pt on preformed Ag/Au core-shell particles by systematically controlling the amount of Ag, Au, and Pt metal precursor solutions. The structural changes (the diameters and increased surface roughness from the defective features) and absorption patterns (the significant reduction of the peak intensities) of the nanoparticles examined with TEM and UV-vis spectroscopy indicated the selective incorporation of Pt on the Ag/Au nanoparticles regardless of their compositions. In addition, a combination of WDX, XRD, and XPS analyses quantitatively and qualitatively confirmed the successful formation of the Ag x Au1Pt2 and Ag4Au1Pt y trimetallic nanoparticles. Subsequently, these series of nanoparticles were deposited on multi-wall carbon nanotubes (MWCNTs) to evaluate their electrocatalytic property in the methanol oxidation reaction (MOR) as a function of their metal compositions. The results showed that the electrocatalytic activities of all Ag4/Au1/Pt y systems were higher than those of typical Pt on the MWCNTs. In particular, the Ag4Au1Pt2 nanoparticles exhibited the highest electrocatalytic property for the MOR, suggesting the importance of the proper combination of metal constituents and structures to regulate the activity in electrocatalytic systems.